Inovasi Pembelajaran Logika-Simbolik melalui Aplikasi DUTAlogic bagi Siswa Tunarungu - Antonius Rachmat Chrismanto; Matahari Bhakti Nendya; Junius Karel Tampubolon; R Gunawan Santosa; Wayan Edi Sudarma; Handi Hermawan (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
Logic is an analysis of methods of thinking. Logic emphasizes the form more than the content of arguments. mathematical logic is often also called the symbolic-logic is a part of mathematics that explores the application of formal logic to mathematics. This has a close relationship with the basic fundamental thinking of mathematics and theoretical computer science.In this research we do three important things, the first is conventional symbolic-logic training for SLB Negeri 1 Bantul. The second step is making of symbolic-logic learning application for deaf students called DUTAlogic and the third is seeing the comparison between conventional learning and learning using the DUTAlogic.Based on data analysis that was done. Thar result show that increase in symbolic logic ability (T) is 50%, increase in the ability of symbolic natural accuracy (N) is 50%. The used of DUTAlogic application is more attractive to deaf students because they feel happier, easier, more-understanding, more concentrated and more creative when doing symbolic-logic learning.